2015
DOI: 10.3141/2493-04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autonomous Vehicle Ownership on Trip, Mode, and Route Choice

Abstract: Autonomous vehicles (AVs) may significantly change traveler behavior and network congestion. Empty repositioning trips allow travelers to avoid parking fees or share the vehicle with other household members. Computer precision and reaction times may also increase road and intersection capacities. AVs are currently being test driven on public roads and may be publicly available within the next two decades; they therefore may be within the span of 20- to 30-year planning analyses. Despite this time scale, AV beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(73 citation statements)
references
References 19 publications
1
72
0
Order By: Relevance
“…Another study showed that a modal shift of up to 1%, mainly from local public transport (bus, light rail, subway) and bicycle, to drivealone and shared-ride modes could be possible because of the ability to multitask in automated vehicles (Malokin, Circella, & Mokhtarian, 2015). Levin and Boyles (2015) confirmed the possibility of increased modal shift from public transport to automated vehicles especially when these vehicles become widely available to travellers with lower value of time. Lamondia, Fagnant, Qu, Barrett, and Kockelman (2016) focused on possible modal shift from personal vehicles and airlines to automated vehicles for long distance travel using Michigan State as case study.…”
Section: Assumptionsmentioning
confidence: 73%
“…Another study showed that a modal shift of up to 1%, mainly from local public transport (bus, light rail, subway) and bicycle, to drivealone and shared-ride modes could be possible because of the ability to multitask in automated vehicles (Malokin, Circella, & Mokhtarian, 2015). Levin and Boyles (2015) confirmed the possibility of increased modal shift from public transport to automated vehicles especially when these vehicles become widely available to travellers with lower value of time. Lamondia, Fagnant, Qu, Barrett, and Kockelman (2016) focused on possible modal shift from personal vehicles and airlines to automated vehicles for long distance travel using Michigan State as case study.…”
Section: Assumptionsmentioning
confidence: 73%
“…Páez et al (2012) found that people with disabilities who have used a car within the past 12 months are about 28% more likely to desire more leisure activities compared to those who have not (Páez and Farber, 2012) Many companies have announced plans to develop self-driving vehicles, and twelve companies have applied to test self-driving cars in California as of 2016 (Chew, 2016). Vehicle automation has the potential to greatly improve travel by reducing congestion, travel times, crashes, and potentially energy consumption (Anderson et al, 2014;Brown et al, 2014;Harper et al, 2016;Levin and Boyles, 2015;Mersky and Samaras, 2016;Wadud et al, 2016). The ability for smart vehicles to interact with smartphones and act as a taxi service to transport people to their destinations also serves as an advantage, reducing travel costs by almost 75 percent (Litman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(), and van Arem, van Driel, and Visser (). This has been utilized in some NDP studies that consider AVs via assumptions of increased capacity in presence of AVs (Chen et al., ; Chen et al., ; Ye & Wang, ) and some other studies of AV impacts using macroscopic traffic assignment models (Levin & Boyles, ; Madadi, van Nes, Snelder, & van Arem, ).…”
Section: Background: Network Design Problem and Automated Drivingmentioning
confidence: 99%
“…Although this is not fully established and there is no consensus in the literature yet, there are studies that claim AD will lead to a lower VoTT (Correia, de Looff, van Cranenburgh, Snelder, & van Arem, ; de Looff, Correia, van Cranenburgh, Snelder, & van Arem, ; Le Vine, Zolfaghari, & Polak, ; Milakis, Snelder, van Arem, van Wee, & Correia, ). This can be considered in the route choice component of macroscopic traffic assignment models via differences in generalized travel cost; see, for instance, Levin and Boyles () and Madadi et al. ().…”
Section: Background: Network Design Problem and Automated Drivingmentioning
confidence: 99%
See 1 more Smart Citation